Architecturally Mediated Allostasis and Neurosustainability: A Proposed Theoretical Framework for the Impact of the Built Environment on Neurocognitive Health - Cleo Valentine; Heather Mitcheltree; Isabelle A. K. Sjövall; Mohamed Hesham Khalil (Brain Sciences)
The global rise in mental health-related disorders represents a significant health and wellbeing challenge, imposing a substantial social and economic burden on individuals, communities, and healthcare systems. According to the World Health Organization, one in four people globally will be affected by mental or neurological disorders at some point in their lives, highlighting a significant global health concern that warrants carefully considered and innovative responses. While mental health challenges arise from complex, multifaceted factors, emerging research indicates that the built environment—the architecture of our homes, workplaces, and public spaces—may exert a critical but underappreciated influence on mental health outcomes. This paper outlines a novel theoretical framework for how visual stressors in the built environment might trigger neurophysiological stress responses via the HPA and SAM axes, potentially contributing over time to allostatic load. In this paper, it is proposed that chronic physiological strain can alter neuroplastic processes and neurogenesis in key brain regions—such as the hippocampus, prefrontal cortex (PFC), anterior cingulate cortex (ACC), and amygdala—thereby affecting cognitive health, emotional regulation, and overall mental wellbeing. Drawing on the principle of neurosustainability, this paper suggests that long-term exposure to stress-inducing environments may create feedback loops, particularly involving the amygdala, that have downstream effects on other brain areas and may be linked to adverse mental health outcomes such as depression. By presenting this framework, this paper aims to inspire further inquiry and applied experimental research into the intersection of neurophysiology, mental health, and the built environment, with a particular emphasis on rigorous testing and validation of the proposed mechanisms, that may then be translated into practical architectural design strategies for supporting health and wellbeing. In doing so, it is hoped that this work may contribute to a more holistic approach to improving mental health that integrates the creation of nurturing, resilient spaces into the broader public health agenda.